Studi Geologi Terhadap Analisis Kestabilan Lereng Menggunakan Metode RMR (Rock Mass Rating) Pada Jalan Daerah Koto Lamo, Kecamatan Kapur Sembilan, Sumatera Barat - Husnul Kausarian; Muhammad Yusuf; Adi Suryadi; Pakhrur Razi; Fitri Mairizki (JURNAL INTEGRASI, 2023)
geographically, the research area is located at coordinates 0°21'12."- 0° 22' 50." latitude and 00°10'53" - 100°33'44.4620" longitude. the study is in the koto lamo and surrounding areas, Kapur Sembilan district, West Sumatra Province. the purpose of this study was to determine the level of slope stability in the study area using the UCS (Uniaxial Compressive Strength) analysis method for intact rock strength, RMR (Rock Mass Rating) and stereographic. From the field data, there are 10 scanlines of the main research objects. Geological mapping shows the slopes are sandstone. From the rock analysis UCS (Uniaxial Compressive Strength), the strength of intact rock the average value of the Schmidt hammer test is 13.08, while the density value of rock samples is 25.86 KN⁄m³. From these results obtained a Uniaxial Compressive Strength (UCS) value of 19 mpa, included in the weight 2 with a weak category. Then the results of the RMR (Rock Mass Rating) analysis are worth 35.4 with RMR class IV (poor).